Enhancing Educational Quality Through Strategic Human Resource Management in Islamic Schools - Aziz, Abdullah Aminuddin; Marlina, Yuli (JURNAL AL-TANZIM, 2025)
This study examines the implementation of Human Resource Management (HRM) in Islamic schools and its impact on educational quality. It aims to identify key factors influencing the effectiveness of HRM and assess its effect on educator performance and learning outcomes. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. The findings indicate that HRM is implemented strategically through precise planning, a focus on pedagogical and technological competencies, methodological alignment with Ministry of Religious Affairs guidelines, and the provision of adequate facilities. Most educators have postgraduate qualifications, and some are pursuing doctoral studies. Continuous evaluation, regular training, and an active pesantren-based learning culture foster a dynamic educational environment. The study concludes that well-structured HRM has a significant impact on improving educator performance and overall academic quality. The findings, as a scholarly contribution, offer valuable insights for faith-based educational institutions seeking to strengthen their HRM practices to improve learning outcomes.